Near‐Infrared‐Responded High Sensitivity Nanoprobe for Steady and Visualized Detection of Albumin in Hepatic Organoids and Mouse Liver. Issue 26 (19th July 2022) - Liu, Guofeng; Wei, Jinsong; Li, Xiaoyu; Tian, Meng; Wang, Zhenxing; Shen, Congcong; Sun, Wan; Li, Chonghui; Li, Xuewen; Lv, Enguang; Tian, Shizheng; Wang, Jihua; et al.
Abstract: Exploring the advanced techniques for protein detection facilitates cell fate investigation. However, it remains challenging to quantify and visualize the protein with one single probe. Here, a luminescent approach to detect hepatic cell fate marker albumin in vitro and living cell labeling with upconversion nanoparticles (UCNPs), which are conjugated with antibody (Ab) and rose bengal hexanoic acid (RBHA) is reported. To guarantee the detection quality and accuracy, an "OFF–ON" strategy is adopted: in the presence of albumin, the luminescence of nanoparticles remains suppressed owing to energy transfer to the quencher. Upon albumin binding to the antibody, the luminescence is recovered under near‐infrared light. In various bio‐samples, the UC NPs‐A b‐R BHA (UCAR) nanoprobe can sense albumin with a broad detection range (5–315 ng mL −1 ). When applied to liver ductal organoid culture medium, the UCAR can monitor hepatocyte differentiation in real time by sensing the secreted albumin. Further, UCAR enables live imaging of cellular albumin in cells, organoids, and tissues. In a CCl4 ‐induced liver injury model, UCAR detects reduced albumin in liver tissue and serum. Thus, a biocompatible nanoprobe for both quantification and imaging of protein in complex biological environment with superior stability and high sensitivity is provided. Abstract : Förster resonance energy transfer‐based UCNPs‐Ab‐RBHA (upconversion nanoparticles‐antibody‐rose bengal hexanoic acid, UCAR) nanoprobe adopts an "OFF–ON" strategy to detect target protein. Under near‐infrared light, UCAR nanoprobe enables protein quantification in vitro and target cell labeling in living cells, organoids, and mouse liver with superior stability and high sensitivity, showing great potential in protein/cell tracking in vivo and clinical diagnosis.